Tracing the policy implementation of commitments made by national governments and other entities at the Third Global Forum on Human Resources for Health. Issue 4 (25th October 2017) - van de Pas, Remco; Veenstra, Anika; Gulati, Daniel; Van Damme, Wim; Cometto, Giorgio
Abstract : We conducted a follow-up analysis of the implementation of the Human Resources for Health (HRH) commitments made by country governments and other actors at the Third Global Forum on HRH in 2013. Since then member states of the WHO endorsed Universal Health Coverage as the main policy objective whereby health systems strengthening, including reinforcement of the health workforce, can contribute to several Sustainable Development Goals. Now is the right time to trace the implementation of these commitments and to assess their contribution to broader global health objectives. The baseline data for this policy tracing study consist of the categorisation and analysis of the HRH commitments conducted in 2014. This analysis was complemented in application of the health policy triangle as its main analytical framework. An online survey and a guideline for semistructured interviews were developed to collect data. Information on the implementation of the commitments is available in 49 countries (86%). The need for multi-actor approaches for HRH policy development is universally recognised. A suitable political window and socioeconomic situation emerge as crucial factors for sustainable HRH development. However, complex crises in different parts of the world have diverted attention from investment in HRH development. The analysis indicates that investment in the health workforce and corresponding policy development relies on political leadership, coherent government strategies, institutional capacity and intersectoral governance mechanisms. The institutional capacity to shoulder such complex tasks varies widely across countries. For several countries, the commitment process provided an opportunity to invest in, develop and reform the health workforce. Nevertheless, the quality of HRH monitoring mechanisms requires more attention. In conclusion, HRH challenges, their different pathways and the intersectorality of the required responses are a concern for all the countries analysed. There is hence a need for national governments and stakeholders across the globe to share responsibilities and invest in this vital issue in a co-ordinated manner.